Keris Mas and the establishment of the ASAS 50's in modern Malay literature - Abu Bakar, Nur Fatiha Fadila (Human Resource Management Academic Research Society, 2024)
This paper is based on observations regarding the significance of the role and influence of the Angkatan Sasterawan 50 (also known as ASAS 5) in shaping the practices of modern Malay literature. Consequently, this paper is dedicated to tracing the history of the emergence and strengthening of the ASAS 50 ideology within modern Malay literature. This is accomplished by providing a serious examination of the key figures of ASAS 50 since its inception. To achieve this objective, the paper utilizes close reading methods. This involves referencing and crossreferencing, particularly concerning Keris Mas, a significant figure in the development and preservation of the ASAS 50 literary ideology of "art for society." Additionally, this paper leverages Charles Wright Mills' theory of The Power Elite to analyze the power dynamics and influence of key figures in mapping the practices of modern Malay literature. The findings reveal that the consolidation of power and the ideology of ASAS 50 have been carried out seriously and consistently over several decades by Keris Mas. This can be illustrated through Keris Mas's authority as an important and influential literary figure in modern Malay literature. This is further evident as Keris Mas has dominated key positions within organizations related to Malay literature, particularly Dewan Bahasa dan Pustaka.